Pengaruh Sanksi Pajak dan Pengampunan Pajak (Tax Amnesty) terhadap Kepatuhan Wajib Pajak Orang Pribadi - Yusuf Pazri; Juitania Juitania; Putri Wulandari; Diana Friska (Universitas Batanghari Jambi, 2026)
This study aims to analyze the effect of tax sanctions and tax amnesty on individual taxpayer compliance. The research was conducted at the Pratama Serpong Tax Service Office. The sample consisted of 400 people, with a random sampling technique. The research data was primary data in the form of distributed questionnaires. The method used was multiple regression. The results of simultaneous and partial testing show that the variables of tax sanctions and tax amnesty significantly affect individual taxpayer compliance at the Pratama Serpong Tax Service Office.